Sistem Informasi Keuangan Pada CV. Bali Indigo Computer - Ryanta, Made (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2021)
The process of making financial reports on the CV. Bali Indigo Computer is still done manually namely, accounting must recap transaction data taken from different Microsoft Excel sheets or files. In addition, the manual process in preparing financial reports is also time-consuming so that there can be delays in preparing financial reports and errors when preparing financial statements. Based on the above background, the formulation of the problem in this research is How to Design and Build a Financial Information System on the CV. Bali Indigo Computer, while the research objective to be achieved in the process of preparing the report is to be able to design and build a company's financial information system. The results of this study, namely to produce a financial information system that aims to assist accounting in making financial reports to determine the company's financial condition. After the system has been built and implemented, the system will then be tested with Blackbox Testing which can assist the company in processing customer data, supplier data, account data, general journal data, transaction data, user data, and financial reports.